Peran Kelompok Tani dalam Pengolahan Limbah Hidrosol Menjadi Pestisida Nabati di Kalurahan Semoyo: Penelitian - Siti Nur Anisah; Ina Fitria Ismarlin; Sari Megawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the level of each variable of learning classes, cooperation vehicles, production units, and treatment of citronella waste and to determine the role of farmer groups in processing citronella waste into vegetable pesticides. The method used in study is a descriptive quantitative method using questionnaires as a research instrument. This study was carried out from November 2024 to March 2025 in Semoyo Village. The selection of the location was carried out by purposive sampling. The sample used in this study was a saturated sample totaling 56 people. The results of the study showed that the role of farmer groups in processing citronella waste into vegetable pesticides in Semoyo Village as learning class was with the value 65,3% and as a vehiche for cooperation was categorized as medium with values 57,6% and groups as production units in the medium category with value 67,3% and the level of processing of citronella waste in the category medium with values 71,1%. Simultaneously, the role of farmer groups as learning classes and cooperation vehicles does not have a significant of citronella waste, while groups as a production unit has a significant effect on the processing of citronella waste.